Akibat Hukum Dari Wanprestasi Dalam Transaksi Pemesanan Hotel di Bali Secara Online - Kristian Ananta Dion; Ni Luh Made Mahendrawati; Desak Gde Dwi Arini (Fakultas Hukum Universitas Warmadewa, 2024)
The rapid advancement of technology has made the task of booking hotel tickets easier for the public. The problem discussed in this research is the case of losses suffered by consumers due to the cancellation of onl reservations made by business actors. This is stated as a problem of default which is a condition of non-fulfillment of achievements or obligations in an agreement. This research is conducted to find out the validity, and the timing of an online hotel booking transaction agreement, especially hotels in Bali. The research method uses normative legal research that examines the problems of legal regulation or legal norm. The result of the research is that consumers have received compensation due to the cancellation of hotel reservations made by business actors. In the Civil Code, it is formulated that negligence in an agreement can be concluded as a default, which is an unlawful act in various forms of default against every obligation imposed in every provision of the applicable law. For the government, the hotel and consumers must have insight into the requirements that apply in the Law regarding default issues in online hotel bookings.